Contemporary monetary policy in China: A move towards price-based policy? - Riikka Nuutilainen (Bank of Finland, Institute for Economies in Transition (BOFIT), 2015)
​This paper focuses on monetary policy in China. A set of different specifications for the monetary policy reaction function are empirically evaluated using monthly data for 1999––2012. Variation is allowed both in the policy targets as well as in the monetary policy instrument itself. Overall, the performance of the estimated policy rules is surprisingly good. Chinese monetary policy displays countercyclical reactions to ination and leaning-against-the-wind behaviour. The paper shows that there is a notable increase in the overall responsiveness of Chinese monetary policy over the course of the estimation period. The central bank interest rate is irresponsive to economic conditions during the earlier years of the sample but does respond in the later years. This finding supports the view that the monetary policy settings of the People's Bank of China have come to place more weight on price-based instruments. A time-varying estimation procedure suggests that the two monetary policy objectives are assigned to different instruments. The money supply instrument is utilised to control the price level and (after 2008) the interest rate instrument has been used to achieve the targeted output growth.
URN:NBN:fi:bof-201503181119
Keywords: E52; E58; 330